Impact of social media on violence reduction in sports stadiums - Al Hammouri, Walid; Al Basheer, Mahmoud (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to identify the role of sports media based on social media in reducing the phenomenon of violence in stadiums from the viewpoint of Sports Science Faculty students at the University of Jordan. A descriptive method was employed, and a sample of 190 students (120 males and 70 females) participated. A comprehensive review of relevant research and collection of pertinent information led to the development of a tailored questionnaire. The instrument consisted of four axes and 24 items, answered using a five-point Likert scale. Statistical data processing was conducted using the SPSS program. The results indicated that, from the students’ perspective, the role of sports media based on social media in reducing violence was moderate. Additionally, statistically significant differences (p<0.05) were found according to gender across all study axes, where males achieved higher arithmetic averages. Significant differences (p<0.05) were also observed according to academic year in the axis of professional commitment to sports media, with second-year students showing higher arithmetic averages. The researchers recommend that sports media based on social media adopt a balanced language when describing matches.